Silymarin plus doxorubicin exerts the anti-hepatocellular carcinoma effects via Wnt, apoptosis, autophagy and angiogenesis pathways - Baohong Yuan; Ruotian Wang; Zehai Gao; Hameed Mirzeei; An-Dong Xiang; Feng Guo (Molecular and Cellular Probes)
Background: The biggest cause of death worldwide is liver cancer. Despite several initiatives and successes in treatment techniques, only a little improvement has been attained. In order to control this cancer, new therapeutic strategies are therefore required. Here, we evaluated the effects of doxorubicin and the milk thistle plant phytochemical Silymarin on liver cancer through apoptosis, autophagy, and Wnt signaling. Methods: Silymarin both alone and together with doxorubicin was administered to induce cytotoxicity in the H22 cell line. qRT-PCR and Western blot analyses, the genes related to autophagy, Wnt signals, and cell death were examined. Results: Doxorubicin and Silymarin both individually and combined dramatically slowed down H22 cells growth. Additionally, there was a significant drop in the Bcl-2 protein and a considerable rise in the caspase 8 and Bax proteins. LC3-I, LC3-II, and Beclin 1 have been all shown to be significantly elevated. Moreover, there was a substantial decrease in the expression of genes involved in the Wnt pathway, including cyclin D1, β-catenin, ZEB1, and Twist. The levels of AMPK were decreased in Silymarin with Doxorubicin alone and in combination, whereas VASP, VEGF, and HIF-1a were lowest. Conclusion: Silymarin may enhance anti-tumor effects of doxorubicin through modulating autophagy, angiogenesis, and apoptosis, in-vitro.